Nursing informatics competence and its associated factors among nurses in Tanzania: a cross-sectional study - Mariam A. Kidayi; Elihuruma Eliufoo Stephano; Ziada Juma Sellah; Mtoro J. Mtoro; Yang Min (BMC Nursing)
Abstract Background Nursing informatics competence has emerged as a critical factor in ensuring high-quality patient care. Developing nations lag in equipping nurses with the informatics competencies to navigate the technologically driven healthcare landscape. Insufficient infrastructure, limited access to technology, and inadequate training programs hinder the development of this competence. This study assesses the nursing informatics competence and its associated factors among nurses in Tanzania. Methods A facility-based cross-sectional study was conducted in Regional Referral Hospitals, and 428 participants were selected through a simple random sampling technique. Data were collected using a structured questionnaire that included the Self-Assessment of Nursing Informatics Competencies Scale (SANICS) to assess competence in computer literacy, informatics literacy, and informatics management skills. Multiple linear regression analysis was employed to determine the relationships between individual and institutional factors that affect informatics competence, using Stata version 18. A p-value of < 0.05 was considered statistically significant. Results The mean score of nursing informatics competencies was 79.58 ± 31.44, while other scores were computer literacy (26.83 ± 9.99), informatics literacy (34.35 ± 13.89), and informatics management (18.39 ± 8.17). The Spearman rank-order correlation revealed significant associations with individual factors, including Information computer technology (ICT) knowledge score (r s=0.7397), ICT attitude score (r s=0.7735), ICT practices score (r s=0.7409), and self-efficacy score (r s=0.7456). On the institutional side, the organization of training (r s=0.7085), management support (r s=0.6877), availability of policies on informatics use (r s=0.6918), ICT infrastructure (r s=0.7181), and human resources (r s=0.6950), a moderate association was observed for workload score (r s=0.4735). Regression analysis identifies several factors, including individual factors such as ICT knowledge score (coefficient = 0.6026, p = 0.023), ICT attitude score (coefficient = 0.7929, p = 0.018), and self-efficacy score (coefficient = 2.2891, p < 0.001). For institutional factors, the training organization (coefficient = 1.2157, p = 0.005) and policies on informatics use (coefficient = 0.8847, p = 0.001) also significantly influence nursing informatics competence. Conclusion This study highlights a critical understanding of nursing informatics competence and its associated factors. The findings underscore the pressing need for targeted educational reforms, notably in ICT, to elevate nurses’ informatics competencies and align them with global health standards.